PENGARUH ORIENTASI PASAR, KEUNGGULAN KOMPETITIF TERHADAP KEBERLAJUTAN USAHA (STUDI PADA PELAKU UMKM DI KOTA WAINGAPU) - Kamunggul, Dorkas Lemba; Situmorang, Tumpal P. (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The influence of market orientation, competitive advantage on the sustainability of MSMEs This research aims to analyze how market orientation in business sustainability and increase competitive advantage in a business. This research method uses a quantitative method that aims to explain the relative relationship between the variables investigated and the effects of other variables. The results of the above research can provide a superior strategy for the sustainability of MSMEs and achieve superior competitiveness in the market.